THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES TOWARD A HEALTHY LIFESTYLE AMONG PATIENTS WITH TYPE II DIABETES MELLITUS AT MEDAN JOHOR COMMUNITY HEALTH CENTER - Reny Indriany Harahap; Pahala Simangunsong; Hartono Hartono (HEARTY, 2026)
Diabetes mellitus continues to increase in prevalence in Indonesia and worldwide. It is a metabolic disorder characterized by chronic hyperglycemia resulting from impaired insulin secretion or insulin resistance. The most common type is Type II diabetes mellitus, which is often associated with lifestyle and dietary patterns. The World Health Organization estimates that the number of patients with diabetes mellitus in Indonesia will reach 21.3 million people. This study aims to determine the relationship between knowledge and attitudes among patients with Type II diabetes mellitus at Medan Johor Community Health Center. This study employed a quantitative method with a cross-sectional approach. The study population consisted of 2,210 patients with Type II diabetes mellitus, with a sample of 100 respondents selected using the Slovin formula. Data analysis was conducted using bivariate and multivariate tests to determine the relationship and influence between variables. The results showed that knowledge (p = 0.003) and attitudes (p = 0.004) had a significant relationship with a healthy lifestyle among patients with Type II diabetes mellitus.